CHALLENGES AND OPPORTUNITIES IN LEVERAGING DIGITAL VISUAL COMMUNICATION FOR PUBLIC RELATIONS IN GOVERNMENT WELFARE SCHEMES: A SYSTEMATIC REVIEW - Sonia; Thakur, Jyotsana (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The integration of digital platforms into government welfare scheme communication represents a paradigm shift in public relations and citizen engagement in the Global South, particularly within the Indian context. This systematic review examines the challenges and opportunities in utilizing digital platforms—including social media, e-government portals, and integrated digital infrastructure—for effective public relations of welfare schemes. Drawing on 56 peer-reviewed sources and emerging case studies from 2012 to 2024, this review analyzes the evolution of digital government communication, stakeholder ecosystem dynamics, and comparative platform efficacy. Findings reveal a complex landscape characterized by opportunities in real-time engagement, inclusive reach, and transparency enhancement, countered by persistent challenges in digital divide mitigation, misinformation management, and equitable access. Theoretical frameworks from Mergel (2012), Hussin et al. (2024), and e-Government 2.0 models provide analytical scaffolding. India’s MyScheme platform (2.34 crore citizens integrated by October 2024) exemplifies both technological advancement and implementation challenges. The paper advocates for a holistic, stakeholder-centric approach integrating multiple digital channels while addressing accessibility, trust-building, and behavioral change mechanisms. Implications extend to policymakers, communications professionals, and development practitioners navigating digital welfare ecosystems in resource-constrained contexts